Periodic detection and disinfection maintenance of dental unit waterlines in dental simulation head model laboratories - Biyao Li; Yuya Hu; Yiqi Wang; Chengqi Zhang; Zimo Wang; Xujie Peng; Jianying Feng (Scientific Reports)
Abstract Dental simulation head model laboratories are crucial for clinical simulation training for stomatological students, yet the maintenance of their dental unit waterlines (DUWLs) has been overlooked. This study investigated water contamination in DUWLs within these laboratories and proposed solutions. Water samples were collected from 12 dental chairs in three laboratories at three time points: the beginning, middle, and end of the semester. At the start of the semester, severe contamination was observed, with colony counts of 11,586 $$\:±\:$$ 1715 CFU/ml for high-speed handpieces and 5375 $$\:±\:$$ 874 CFU/ml for three ways syringes. As the semester progressed, colony counts gradually decreased but remained above clinical thresholds. Both 20 mg/L organochlorine disinfectant and 20 mg/L chlorine dioxide were effective in reducing bacterial contamination below standard ranges three days post-disinfection. Microbial diversity analysis revealed Proteobacteria and Bacteroidota as the dominant bacterial phyla, with Ascomycota as the dominant fungal phylum. Potentially pathogenic bacteria such as Pseudomonas, Burkholderia-Caballeronia-Paraburkholderia, Ralstonia, Mycobacterium, Legionella, Paenibacillus, Streptomyces, Acinetobacter, and Prevotella, as well as fungi like Fusarium and Penicillium, were detected. Therefore, urgent attention is needed to address DUWL contamination in dental laboratories, and it is recommended to disinfect DUWLs using either 20 mg/L organochlorine disinfectant or 20 mg/L chlorine dioxide every three days.